2017
DOI: 10.1007/s00268-017-3963-1
|View full text |Cite
|
Sign up to set email alerts
|

Extralevator Abdominal Perineal Excision Versus Standard Abdominal Perineal Excision: Impact on Quality of the Resected Specimen and Postoperative Morbidity

Abstract: ELAPE may be safely implemented into routine clinical practice with no increase in postoperative morbidity and considerable improvements in the quality of the resected specimen of patients with low rectal cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 37 publications
2
33
0
Order By: Relevance
“…In addition, our results showed that 5-year OS and DFS rates were poorer for LRC patients compared with M/HRC patients after laparoscopic surgery, which is consistent with previous literatures [10,14], although these studies were not focused exclusively on laparoscopic surgery. Chiang et al [10] noted that the rectal cancer level signi cantly affected the long-term survival and patterns of distant metastases for patients who underwent surgical resection.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, our results showed that 5-year OS and DFS rates were poorer for LRC patients compared with M/HRC patients after laparoscopic surgery, which is consistent with previous literatures [10,14], although these studies were not focused exclusively on laparoscopic surgery. Chiang et al [10] noted that the rectal cancer level signi cantly affected the long-term survival and patterns of distant metastases for patients who underwent surgical resection.…”
Section: Discussionsupporting
confidence: 92%
“…Compared with mid-rectal and upper-rectal cancers, LRC had the worst prognosis. Cheng et al [14] divided T3/T4 rectal cancer patients who underwent surgery into high and mid/low rectal cancer, they found that patients with stage III high rectal cancer demonstrated better prognosis than those with mid/low rectal cancer, and tumor location was an independent prognostic factor for long-term survival. However, other studies have come to different conclusions, meaning that tumor location has no in uence on long-term outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27][28] An additional of 4 studies with full text of the original paper only were included. 9,10,29,30 Eleven studies without separate data for OP, [31][32][33][34][35][36][37][38][39][40][41] and 1 study that eventually appeared to have included only 1 patient with OP 42 were excluded.…”
Section: Literature Search and Selectionmentioning
confidence: 99%
“…APR or ELAPE was recommended when the levator muscle was invaded or preservation of the anus was impracticable. The perineal surgery and terminal colostomy were performed as described in the literature [14].…”
Section: Interventionsmentioning
confidence: 99%